Uji Aktivitas Antibakteri Ekstrak Etanolik Daun Mengkudu (Morinda Citrifolia L.) Terhadap Bakteri Streptococcus Pyogenes secara In Vitro - Retno Priamsari, Margareta; Rokhana, Almira (Jurnal Farmasi (Journal of Pharmacy), 2020)
Pharyngitis is a disease that is included in the Upper Respiratory Tract Infection (ISPA). The most common bacteria in acute pharyngitis is Streptococcus pyogenes. Plants that have antibacterial properties are noni (Morinda citrifolia L.). This study aims to determine the minimum inhibitory level (MIC) of S. pyogenes antibacterial activity in vitro. Extraction by remaceration method using ethanol 96% solvent. The Kirby-Bauer method for antibacterial testing used BAP media inoculated by means of a spread plate. The treatment group used a positive control (amoxicillin 25 µg); negative control (sterile distilled water); Noni leaf extract with a concentration of 1.25%, 2.5% and 5%. Replication was carried out 3 times. The parameters observed were the inhibition zone formed around the disc paper. The data obtained were analyzed statistically using Kruskall-Wallis followed by Mann-Whitney with a confidence level of 95%. The results showed that the noni leaf extract contained saponins, triterpenoids, tannins and phenols. Noni leaf extract had a significant effect (p≤0.05) on S. pyogenes. The 2.5% concentration had the smallest activity with an average inhibition zone diameter of 5.83 mm.